Comprensión lectora en estudiantes de tercero y cuarto grado de primaria en Ventanilla - Modesto Masías, Vilma (2012)
The purpose of the research was to establish the level in reading comprehension of students in third and fourth grade in Ventanilla. The design corresponds to a simple descriptive research; the sample was 620 students type available. The instrument used is the LLECE reading comprehension test. Data were analyzed using descriptive statistics. Arriving at the following results: In reading comprehension students in third and fourth grade took places at three levels: the 94.68% of students took places in primary literal reading, the 88.23% of students took places in reading mode literal paraphrases and 62.42% of students achieved settle at inferential character reading.